Designing of YouTube Access Interface for Institutional Digital Repository - Mandal, Sukumar (Journal of Information and Knowledge, 2019)
YouTube is a video-sharing website. It allows users to upload, view, rate, share, add to favorites, report, comment on videos, and subscribe to other users and offers a wide range of user-oriented and education-related videos. Digital resource is growing and digital libraries will include digital materials that subsist outside the physical and administrative bounds of any one digital library. Even though digital libraries include all traditional processes, these have to be revised and enhanced to accommodate the differences between digital media and traditional media. This paper describes a system that can describe and manage digital resources in libraries.